Histamine stimulates neurogenesis in the rodent subventricular zone - Bernardino, Liliana (2018)
Neural stem/progenitor cells present in the subventricular zone (SVZ) are a potential source of repairing cells after injury. Therefore, the identification of novel players that modulate neural stem cells differentiation can have a huge impact in stem cell-based therapies. Herein, we describe a unique role of histamine in inducing functional neuronal differentiation from cultured mouse SVZ stem/progenitor cells. This proneurogenic effect depends on histamine 1 receptor activation and involves epigenetic modifications and increased expression of Mash1, Dlx2, and Ngn1 genes. Biocompatible poly (lactic-co-glycolic acid) microparticles, engineered to release histamine in a controlled and prolonged manner, also triggered robust neuronal differentiation in vitro. Preconditioning with histamine-loaded microparticles facilitated neuronal differentiation of SVZ-GFP cells grafted in hippocampal slices and in in vivo rodent brain. We propose that neuronal commitment triggered by histamine per se or released from biomaterial-derived vehicles may represent a new tool for brain repair strategies. STEM CELLS 2012; 30:773784